Activation of the Nrf2 Signaling Pathway as a Therapeutic Strategy Against Periodontal Disease: A Narrative Review - Sarmistha Saha; Nadezhda Sachivkina; Ekaterina Lenchenko; Olga Pilshchikova; Alexandr Muraev (Dentistry Journal, 2025)
Periodontitis (PD), is a chronic inflammatory disease of the periodontal system, which includes gingiva, periodontal ligament, alveolar bone, and tooth cement. It is becoming increasingly prevalent globally, and its implications for oral health are profound. The Nrf2 signaling pathway is crucial in managing the relationship between inflammation and oxidative stress, making it vital for understanding this disease. Nrf2 interacts with key redox-sensitive inflammatory pathways, playing a vital role in the development of periodontitis. Acknowledging these dynamics underscores the importance of proactively addressing the complex aspects of periodontal disease. This review emphasizes its intricate interactions with redox-sensitive transcription factors vital for sustaining the self-perpetuating inflammatory processes underlying the disease. Additionally, it explores promising therapeutic strategies aimed at Nrf2 activation and encourages more effective management of PD.